Building Sustainable Worlds : Latinx Placemaking in the Midwest - Fox, Claire F.; Cadava, Geraldo L., 1977-; Rivera-Servera, Ramón H., 1973-; Delgadillo, Theresa, 1959- (Book collections on Project MUSE., 2022)
"Latina/o/x places exist as tangible physical phenomena but also as sites built and maintained by creative cultural practices. In this collection, an interdisciplinary group of contributors examines how the many ways we conceive of our communities shape those places. At the same time, our embodied experiences of place form how we imagine and reimagine our surroundings. Placemaking helps sustain communities in the current atmosphere of xenophobia and racism through cultural expression ranging from festivals to zines to sanctuary movements. It emerges not only in specific locations but as movement within and between sites; not only as part of a built environment, but also as an aesthetic practice; and not only because of efforts by cultural, political, and institutional leaders, but through mass media and countless human interactions. A rare and crucial perspective on Latina/o/x people in the Midwest, Building Sustainable Worlds reveals how expressive culture contributes to, and sustains, a sense of place in an uncertain era"--